The Role of the General Election Commission (KPU) of Karanganyar in Increasing Voter Participation in the 2024 Presidential and Vice Presidential Elections and Legislative Elections - Farco Siswiyanto Raharjo; Purbayakti Kusuma Wijayanto; Febri Yudistira (Indonesian Journal Publisher, 2025)
The General Election Commission (KPU) as one of the organizers of the general election, has strategic and tactical duties. This is in accordance with Article 2 of Law number 7 of 2017 concerning general elections. The General Election Commission (KPU) Karanganyar is the election organizer based in Karanganyar Regency. As the election organizer, the General Election Commission (KPU) Karanganyar is tasked with conducting elections and regional head elections based on the provisions regulated by law. This research aims to describe the role of the Karanganyar General Election Commission in increasing voter participation in the 2024 presidential, vice-presidential, and legislative elections. This research method is qualitative. In this research, the technique used for selecting informants is purposive, which falls under the category of non-probability sampling. The researchers considered using this technique because the informants have a capacity for information mastery and careful consideration of the research focus. The collected data will then be analyzed using interactive analysis techniques. The role of the Regulator is carried out through various regulations used by the General Election Commission of Karanganyar Regency to enhance public participation in exercising their voting rights in the 2024 presidential and legislative elections. These regulations are included in the General Election Law, the Decision of the Indonesian General Election Commission (KPU RI), and the Regulations of the Indonesian General Election Commission (KPU RI).The role of the Facilitator is carried out through the Facilitation of the Karanganyar Regency General Election Commission in order to increase voter participation through the Student Council President Election (MILKOI). The General Election Commission (KPU) of Karanganyar Regency facilitated the organization of student council president elections in high schools and equivalent institutions in Karanganyar Regency. The role of the catalyst has been carried out by the General Election Commission (KPU) of Karanganyar Regency. The role of the catalyst includes organizing socialization for community groups about the stages of the general election, recruiting democracy volunteers, intensive communication with stakeholders, and optimizing the recruitment of Ad Hoc bodies based on socialization to the community and social media.